Peran Penyuluh Pertanian dalam Pemberdayaan Petani Muda Pada Program YESS (Youth Entrepreneurship and Employment Support Services) Di Desa Tatah Pemangkih Laut Kecamatan Kertak Hanyar Kabupaten Banjar - Shafrina Amalia (Jurnal PubBis, 2026)
The decline in the number of young farmers in Indonesia, including in Tatah Pemangkih Laut Village, Kertak Hanyar District, Banjar Regency, poses a serious challenge to the sustainability of the agricultural sector. The government, through the Youth Entrepreneurship and Employment Support Services (YESS) Program, seeks to promote farmer regeneration with agricultural extension workers as the main facilitators. This study aims to describe the role of agricultural extension workers in empowering young farmers through the YESS program. A qualitative descriptive method was applied, using interviews and documentation, with thematic analysis of data obtained from six agricultural extension workers and six farmer group leaders. The findings reveal that extension workers play significant roles as mentors, organizers, technicians, consultants, and dynamizers. They enhanced young farmers’ capacities through training, technical assistance, and facilitation of access to capital and markets. However, challenges remain, including the predominance of one-way communication and the lack of program sustainability, which limit active participation and the integration of local knowledge. In conclusion, agricultural extension workers are crucial in fostering young farmers’ interest and independence, yet more participatory and collaborative approaches are needed to ensure that the YESS program effectively produces resilient, innovative, and competitive millennial farmers.